A Total Social Cost Approach to Public Transport Planning in South Africa - Nkosi, Muzi (Department of Civil Engineering, 2024)
Public transport has a significant role in addressing economic, social and environmental issues resulting from motorised mobility. Motorised travel, including that offered by public transport, has positive and negative impacts. It is particularly true in the case of public transport that the magnitude of the impacts is a function of how resources are allocated as well as of the spatial arrangement of transport options to service the demand. In the past, the allocation of modes of travel to service demand along corridors has primarily been based on the evaluation of marginal economic benefits. The emphasis is placed on net economic costs, despite the presence of external costs generated by the transport system and that are ultimately borne by society. External costs include costs due to accidents, pollution, noise, visual intrusions and amenity losses. Appraising transport interventions solely on the basis of net economic benefits (operator costs) is insufficient to meet the goals set out in the White Paper on National Transport Policy, which requires the provision of transport infrastructure and services to be in line with sustainability goals (DoT, 1996 & 2017). Fundamentally, Section 24 of the Constitution bestows ecologically sustainable development the status of a human right. This thesis evaluates the effectiveness of a total social cost (TSC) approach to guide the selection of a public transport mode to service passenger travel demand along a given corridor. By definition, total social costs comprise internal and external costs. Internal costs include all the costs borne directly by the consumer of the good or service in question, whilst external costs are borne by society, including costs such as the risk of accidents and emissions. The external costs can be significant. For example, it is estimated that, in the European Union, the proportion of external costs as a percentage of GDP ranges from 3.4% in Norway to over 7% in Portugal and Luxemburg (European Commission, 2019). Welfare theory argues that an optimal price charged to the users should also reflect external costs, and the failure to internalise external costs means that the use of the transport system is inefficient (Maibach et al., 2008). To this end, the work in this thesis is important because it may be used to facilitate the internalisation of public transport-related costs through the use of regulations-based and/or market-based instruments. In this thesis, the effectiveness of the total social cost (TSC) approach to guide the provision of transport infrastructure and services was evaluated against the conventional modal hierarchy approach for the development of the Atteridgeville-Pretoria CBD corridor. The total social cost (TSC) approach suggest that effective road-based public transport modes for the 18 km corridor are as follows, measured in terms of passengers per hour per direction: • minibus taxi (0-2 000), iv | P a g e • standard bus (2 000- 4 000), • articulated bus (4 000- 8 000), and • BRT standard bus greater 6 500. The most effective mode for the Atteridgeville-Pretoria CBD corridor turned out to be the BRT standard bus when assessed using the total social cost approach. On the other hand, it was found to be an articulated bus when applying the modal hierarchy approach. Society would pay R4.70 to produce a passenger-kilometre of BRT standard bus service. However, if the assessment had been only based on marginal operator costs, the articulated bus would cost the least when compared to the other technologies. The operator costs would amount to R3.05 in order to produce a passengerkilometre of articulated bus service. However, the marginal total social cost for an articulated bus was R5.20, which is higher in comparison to that of the BRT standard bus service. In addition, the study found that marginal external cost (measured rand per passenger-km) ranged from 0.6% for a commuter rail service to 6% for a minibus taxi. The failure of planning approaches to capture these external costs and user costs might have undesired consequences in the long term. For instance, for the Atteridgeville- Pretoria CBD corridor case study, when assessing based-on operator cost, it was estimated that the effective mode is the articulated bus. However, when assessed for total social costs, it was the BRT standard bus. The total social cost imposed by the articulated bus resulted from high user costs compared to the BRT standard bus. From the analysed corridor, the total social cost approach is important in unpacking the trade-off required to determine the transport mode required to service demand along a corridor. The modal hierarchy does not explicitly detail the trade-offs between the operator, user and external costs. The lack of detail might then result in unintended consequences in the long term.